(untitled) (Journal of Medicine, 2012)
Choledochal cyst is an aneurysmal dilatation of the bile duct. It is a rare condition. Here we report a case of choledochal cyst in a 15 year-old female patient. She presented to the out patient clinic with the complaints of recurrent pain and lump in the upper abdomen along with fever for 1 year. The diagnosis was made by abdominal ultrasound complemented by computed tomography. DOI: http://dx.doi.org/10.3329/jom.v13i1.10091 JOM 2012; 13(1): 120-122